Additional Fish Record From the Uscari Formation, Upper Miocene-lower Pliocene of Costa Rica: a Chimaeroidei Tooth Plate (Pisces, Chondrichthyes, Holocephali) - Laurito, César A. (Universidad de Costa Rica, 2007)
.